How to understand sovereignty through the prism of cosmopolitan morality - Sarıkaya, Yağız Kağan (Graduate School, 2024)
Human history is shaped by complex dynamics influenced by major transformations and divisions. These dynamics have continuously altered political, economic, and cultural structures, guiding the evolution of social organizations. Throughout history, humanity has formed various political and social units in response to changing needs, and these units have undergone transformations based on social, cultural, and moral developments. Tribes, religious communities, trade unions, political parties, and states represent historical examples of social groups, each with its own rules, structures, and definitions. To understand the concept of sovereignty, it is essential to explore its philosophical trajectory and evolution. Sovereignty is traditionally defined as the state's authority to exercise its will independently within its borders, free from external interference. However, globalization, social inequalities, environmental disasters, pandemics, and wars have necessitated a reevaluation of sovereignty. While modern states maintain their independence within national borders, these global challenges require increased international cooperation and collective solutions. Therefore, the concept of sovereignty must be reconsidered in light of current global conditions. From a global perspective, sovereignty is no longer confined to internal matters of states but has become a shared issue for individuals and the international community. This paper examines how sovereignty can be reinterpreted in a global context and its implications for social and political structures. It is based on the assumption that the traditional notion of sovereignty is inadequate and that new institutional and political approaches are required. Sovereignty, especially with the Peace of Westphalia and the revolutions of the 18th century, has been grounded in the nation-state system. Today, it emphasizes the right of states to maintain independence within their borders and to be protected from external interference. While this principle has underpinned nationalism and nation-state politics, global developments since the 20th century have shown that sovereignty cannot be limited to internal issues. The process of globalization, increasing international trade, the rapid flow of information, environmental crises, and human rights violations require a reassessment of state sovereignty. Many modern issues are transnational, prompting a shift towards international collaboration and a more collective, global approach to sovereignty. Cosmopolitan morality, which advocate for the universal rights and equality of all humans, should extend into political theory as cosmopolitan sovereignty. This idea moves beyond the sovereignty of nation-states, proposing a global political union centered on individual rights and freedoms. In this view, human rights violations should be seen as a global issue, not just a domestic one. This requires a sense of responsibility beyond national borders and emphasizes international solidarity. Today's global challenges, such as climate change, pandemics, armed conflicts, and poverty, cannot be addressed within the confines of nation-states alone. Cosmopolitan sovereignty suggests that solving such issues requires international cooperation, with states acting together based on shared values. The implementation of cosmopolitan sovereignty, however, is a difficult process, as it involves balancing national sovereignty with global justice and equality. States must adopt a collective approach to global issues while still safeguarding national interests. Human rights, as a fundamental aspect of cosmopolitan sovereignty, are not limited to the internal affairs of nation-states but are universal rights for all humanity. The protection of these rights is a global responsibility, as human rights violations have increasingly become a global issue. For example, environmental disasters, such as climate change, affect not only local or national populations but pose a global threat. The actions of countries emitting the most carbon affect vulnerable regions and exacerbate global inequalities. This environmental injustice calls for the need for environmental justice and the protection of human rights. Global problems, such as the refugee crisis, wars, and ethnic cleansing, also transcend national boundaries. These issues demand international cooperation and solidarity, as they affect entire regions or the global community. The Covid-19 pandemic, for instance, demonstrated how a health crisis could quickly spread across borders, affecting social, economic, and cultural connections globally. These challenges require collective action based on shared moral values, as they are no longer the sole concern of individual nations but of the entire international community. Cosmopolitan sovereignty thus challenges the traditional notion of sovereignty based on nation-states, advocating for a global perspective. It calls for a normative framework that transcends national borders, urging the international community to collaborate on global issues, including human rights, environmental protection, and global peace. Sovereignty, from this cosmopolitan standpoint, is not merely a theoretical concept but a practical responsibility that requires global cooperation. International solidarity and cooperation are essential for addressing global challenges and ensuring justice, equality, and sustainability. The inadequacy of the current definition of sovereignty arises from its reliance on a geopolitical understanding rooted in the concept of the nation-state. Instead, sovereignty should be defined through a perspective of power that is based on cosmopolitan morality and requires all individuals to act as part of a global and environmental community, encompassing a set of principles that draw from both utilitarian and deontological approaches. The concept of national sovereignty is inherently contradictory. This constitutes a two-level problem: one at the ideal level, and the other in practical terms. In practice, this concept needs to be criticized, as it contradicts the necessity for equal consideration of interests. In this context, institutionalization is essential. There is a need to focus on the concerns about the pressures that power can create and to build a critical mindset. It is necessary to argue for a critical public space in order to ensure secure cosmopolitan institutionalization and reduce the risk of corruption. Furthermore, if institutionalization is to occur, it is crucial to develop a framework of thought that examines the behavior of these institutions in a holistic manner. If cosmopolitan morality are grounded in a foundation that does not include a critical mindset, they could turn into a source of oppression. Therefore, a critical mindset is required; otherwise, there is a risk of a shift from cosmopolitanism to particularism. In conclusion, the fight against global problems requires moving beyond the traditional understanding of sovereignty and adopting a broader humanitarian perspective. The principles of human rights, equality, and environmental protection are global responsibilities. Therefore, every individual and state must contribute to this responsibility and act toward common global goals. Cosmopolitan sovereignty extends beyond national borders to encompass the entire global community. This approach necessitates a new normative framework, a shared ethical system, and international cooperation to address global crises. In this context, cosmopolitan sovereignty is not only a moral stance but also a practical necessity for safeguarding human rights, protecting the environment, and establishing global peace.
Kozmopolitan ahlak yansımasında egemenliği nasıl anlamalı
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2024
Keywords: national sovereignty; milli egemenlik; political philosophy; siyaset felsefesi; nation-state; ulus-devlet